(untitled) (Journal of Engineering, 2023)
The manifestations of climate change are increasing with the days: sudden rains and floods, lakes that evaporate, rivers that experience unprecedentedly low water levels, and successive droughts such as the Tigris, Euphrates, Rhine, and Lape rivers. At the same time, energy consumption is increasing, and there is no way to stop the warming of the Earth’s atmosphere despite the many conferences and growing interest in environmental problems. An aspect that has not received sufficient attention is the tremendous heat produced by human activities. This work links four elements in the built environment that are known for their high energy consumption (houses, supermarkets, greenhouses, and asphalt roads) according to what is known as the energy synergy to share them within a thermal network independent of the national network. This research concluded that an asphalt road with a length of 6 km is sufficient to heat more than 800 homes, in addition to valuable benefits accrued by hot countries, such as maintaining the quality of the asphalt layer, prolonging its life, and reducing traffic accidents. The supermarket, which needs cooling every day of the year, can meet its energy needs for cooling in the winter by heating the Greenhouse, while the heat flux is stored for each of the greenhouses and the supermarkets for the rest of the year in the thermal tank (TESS). لتدفق الحراري لكل من الدفيئة والسوبر ماركت لبقية العام في الحرارية. خزان (TESS).